Kitchen Pollutants Control and Ventilation A Ventilation Guide to Asian & European Kitchen Environment - Li, Angui; Kosonen, Risto (Springer Nature Singapore : Imprint: Springer, 2019)
This book has been written by two experts in ventilation and indoor air quality with vast experience in the field of kitchen ventilation in both Asia and Europe. The authors share their extensive knowledge of the subject and present the results of their research programs as well those of other researchers. Discussing advanced theories of and design approaches for kitchen ventilation, it is a useful reference resource for a wide range of readers, including HVAC researchers, designers and architects.